Power and influence in world-level sport coaching: A Foucauldian and Raven-informed interpretive vignette study in underwater rugby - Samuel José Gaviria-Alzate; Claudia Arcila-Rojas; Luis Álvarez González; Juliana Posada Monsalve; Jonnathan Arenas Taborda; Lina Restrepo; Wilder Geovanny Valencia-Sánchez (PLoS ONE, 2026)
This study examined how world-level underwater rugby coaches mobilise interpersonal power to shape athletes’ behaviour, cohesion and self-regulation under high-pressure, low-verbal conditions. Anchored in Foucauldian accounts of power/knowledge and Raven’s interpersonal power bases, we examined how trust, expertise and authority were narrated within an embodied coaching ecology. An interpretive qualitative vignette design with a hermeneutic sensibility was employed with three world-champion coaches (aged 42–44; ≥ 12 years’ international experience). Data were generated via an online questionnaire comprising ten high stakes coaching scenarios. For each vignette, participants selected the single response option that best approximated their likely first-line action (mapped at design time to French and Raven’s power bases, including informational power) and provided a brief open-text rationale. Analysis combined a deliberately modest descriptive use of the closed selections with reflexive thematic analysis of the written rationales, treating the taxonomy as a sensitising framework at interpretation. Three themes captured coaches’ influence work: relational anchoring under aquatic risk; expertise as embodied pedagogy, in which brief reasons were folded into demonstration; and boundary-setting governance, in which formal authority was framed as selective and proportionate. The contribution is not a general revision of power theory, but a context-specific refinement. In low-verbal aquatic settings, influence was narrated as a compressed choreography in which referent trust opens receptivity to expert demonstration, informational reasoning is nested within expert guidance, and formal authority operates mainly as a bounded safety and standards resource.